The Encyclopaedia of Islam: C-G (Vol.2) - Edited by Lewis, B. [et al.] (Leiden, Neitherland E. J. Brill, 1991)
For more information about the Encyclopeadia of Islam Online visit www.brillonline.nl to view a free demo or to place your order.
Includes Illustrations
Keywords: Islamic civilization